Levels of PCDDs, PCDFs and dl-PCBs in the blood of childbearing-aged women living in the vicinity of a chemical plant in Tianjin: A primary study. (January 2015) - Chen, Xi; Chen, Jing-shan; Zhang, Lei; Li, Jing-guang; Yao, Lena; Self, Steven G.; Sun, Xin; Tang, Nai-jun
Highlights: Dioxins and dl-PCBs in serum from Chinese women in childbearing age. High levels up to 155 pg WHO 2005 TEQ g −1 lipid have been found. Levels increase with decreasing distance from a chemical plant. This pilot study provides basic information for future epidemiological studies. Abstract: Several studies have suggested that maternal exposure to Polychlorinated dibenzo-p-dioxins (PCDDs), poly-chlorinated dibenzofurans (PCDFs) and dioxin-like polychlorinated biphenyls (PCBs) may affect foetal growth and infant development. The aim of our study was to determine whether the childbearing-aged residents living near a chemical plant have a greater exposure risk. Concentrations of 17 PCDD/Fs congeners and 12 non-ortho and mono-ortho dioxin-like PCBs were measured using HRGC-HRMS in the blood of 30 non-occupational childbearing-aged women living near a chemical plant (Dagu) that had been producing chlorinated pesticides from 1958 to 2004. The factors that influenced the body burden were investigated based on responses to a questionnaire. Levels of PCDD/Fs + PCBs were in the range of 16.43–155.29 pg WHO 2005-TEQ g −1 lipid. PCDDs and PCDFs contributed 56.72% and 34.44%, respectively, to the total TEQ value. Total WHO-TEQ was approximately tenfold higher in the participants living in the vicinity of the plant (distance: 1.52 ± 0.148 km) than in the groups living farther away (distance: 4.93 ± 1.124 km). A negative correlation between total WHO-TEQ and distance to Dagu was observed by multiple linear regression models. The data provide basic information for monitoring dioxin-like chemicals in the district and for the future study of the relationship between POPs and pregnancy outcomes.